Low-temperature sanitary ceramic green body, preparation method thereof and low-temperature sanitary ceramic
By introducing natural micro-nanofibrous tremolite into the sintered sanitary ceramic blank in low-temperature sintered sanitary ceramic blank to replace dolomite, the phase composition of the blank system is optimized, the problems of unstable sintering deformation and easy cracking during the molding process are solved, stable deformation control and strength improvement are achieved, the range of sintering is broadened, and the stability of product quality is improved.
Patent Information
- Application Number
- CN202411739247.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
During the sintering process, existing low-temperature sintered sanitary ceramic body has problems such as unstable deformation, difficulty in controlling dimensional tolerances, and fluctuations in product quality pass rate. The introduction of dolomite leads to poor suspension of mud and prone to cracking during molding.
By introducing natural micro-nanofibrous tremolite, it replaces the calcium-magnesium raw material dolomite, and serves as a calcium-magnesium source for the low-temperature synthesis of sodium/calcium feldspar and other crystals in the low-temperature blank material system, the phase composition of the blank system is optimized, the liquid phase viscosity is improved, the sintering deformation time is shortened, and the sintering range is broadened.
The stable deformation control of the sintered sanitary ceramic blank is achieved, the range of sintering is broadened, the tensile ability and strength of the blank is improved, the cracking problem during molding and sintering is solved, and the stability of product quality and the feasibility of industrial application is improved.
Smart Images

Figure BDA0005162238760000041 
Figure BDA0005162238760000042 
Figure BDA0005162238760000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sanitary ceramic production, and in particular to a low-temperature sanitary ceramic blank and a preparation method thereof, and low-temperature sanitary ceramic. Background Art
[0002] Sanitary ceramics are usually sintered at a high temperature of 1200-1250℃. The sintering stage consumes more than 50% of the energy in the entire life cycle and produces more than 50% of carbon emissions. In order to reduce energy consumption and carbon emissions, reducing the sintering temperature of sanitary ceramic body materials and expanding the sintering temperature range of materials is one of the most effective methods.
[0003] Porcelain green body material is the mainstream green body material of sanitary ceramics at present. It is generally sintered from a ternary raw material system of quartz-feldspar-clay, with a water absorption rate of less than 0.5%. Its physical phase composition is mainly mullite, quartz and a large amount of glass phase. The melting and flow of the glass phase reduce the porosity of the green body and increase the density to complete the sintering, while the formation of mullite increases the viscosity of the melt liquid phase and reduces the deformation of the green body. At present, the deformation problem that restricts the key technology of low-temperature sintering of sanitary ceramics is generally solved by increasing the dosage of traditional flux components such as MgO, CaO, K2O and Na2O and introducing new high-efficiency flux components such as Li2O and B2O3, reducing the sintering temperature, and synthesizing the nucleation and growth of low-temperature new crystal phases.
[0004] CN113929437A discloses a low-temperature sintered sanitary ceramic body and a preparation method thereof. The ceramic body is added with raw materials such as dolomite and boron calcium waste glass to form a sodium / calcium feldspar (i.e., labradorite, Al 1.775 Ca 0.64 Na 0.32 8S 2.275 ) crystals as the main crystal phase of the green body, and the liquid phase viscosity of the green body system is greatly improved by introducing Li2O and B2O3 flux components, effectively controlling the low-temperature sintering deformation. However, the microscopic morphology of dolomite is granular, with poor suspension, and it is easy to flocculate during the molding process, which affects the uniformity of the ceramic green body and easily causes problems such as green body cracking; but the main shortcoming of this system is that it significantly slows down the necessary glass liquid phase formation rate, causing the maximum densification time to lag, that is, the time required to reach the maximum steady-state deformation is longer, and the firing range becomes narrower, making it more difficult to control dimensional tolerances and regularity, and the product quality qualification rate fluctuates, which greatly increases the difficulty of industrial application of technological achievements. Summary of the invention
[0005] The present invention aims at the above problems, makes up for the deficiencies of the prior art, and provides a low-temperature sintered sanitary ceramic body and a preparation method, and low-temperature sanitary ceramics to solve the problems arising from the above background technology.
[0006] The first aspect of the present invention provides a low-temperature sintered sanitary ceramic body, comprising the following raw materials in mass fractions: 10-20% ball clay, 10-25% high-alumina porcelain stone, 5-15% spodumene tailings or microcline, 25-45% porcelain clay, 0-10% potassium feldspar, 5-20% tremolite, and 5-20% boron-containing waste glass.
[0007] The present invention optimizes the SiO2-Al2O3-CaO-MgO-K2O-Na2O-Li2O-B2O3 with sodium / calcium feldspar as the main crystal phase.
[0008] The 1100°C low-temperature sintering (water absorption rate ≤ 0.5%) sanitary ceramic blank system introduces natural micro-nano fibrous tremolite to replace the calcium-magnesium raw material dolomite as the calcium-magnesium source for the low-temperature synthesis of sodium / calcium feldspar and other crystals in the low-temperature blank material system, so that the low-temperature sintering ceramic slurry has better molding performance, improves the tensile strength of the wet blank and the dry blank, and solves the problems of poor slurry suspension caused by the introduction of a large amount of granular dolomite and easy cracking during the blank forming process. The natural micro-nano tremolite fibers are widely and evenly distributed in the system, which can make the CaO and MgO components with fluxing effect play a better fluxing effect, shorten the time required for the blank to reach the maximum deformation, broaden the sintering range of the low-temperature sintered blank, and ensure that the sodium / calcium feldspar and other crystal phases can be widely and evenly synthesized in the system at low temperature, improve the system liquid phase viscosity, reduce sintering deformation, and improve the strength of the blank. The present invention makes the SiO2-Al2O3-CaO-MgO-K2O-Na2O-Li2O-B2O3 low-temperature sintered sanitary ceramic blank system more adaptable to the needs of practical applications, and promotes the sanitary ceramic industry to achieve energy saving, consumption reduction and emission reduction.
[0009] Preferably, the chemical composition of the blank is as follows: SiO2: 50-60%, Al2O3: 15-25%, Fe2O3: 0.5-1.5%, TiO2: 0.3-1%, CaO: 4-9%, MgO: 1-6%, K2O: 2-4%, Na2O: 0.2-1.5%, Li2O: 0-0.5%, B2O3: 0.3-1.5%, loss on ignition: 5-12%.
[0010] Preferably, the molar ratio of SiO2 to Al2O3 is (4-6):1, and the molar ratio of K2O to (Na2O+Li2O) is (2-6):1.
[0011] Preferably, tremolite is a fibrous crystal with a fiber length D50 of 10-30 μm and a diameter of ≤0.5 μm.
[0012] In the present invention, tremolite is a fiber structure (such as Figure 4As shown in the figure, it can improve the suspension of the slurry, increase the tensile strength, and reduce the cracking during forming and the cracking during sintering. In addition, this natural micro-nano fiber structure provides a nucleation reaction matrix for the in-situ growth of crystals during the sintering reaction, and provides Si, Al, Ca, and Mg sources for newly synthesized crystals such as sodium / calcium feldspar, shortening the reaction path and reaction time, thereby promoting the sintering reaction to be completed at a lower temperature.
[0013] The second aspect of the present invention provides a method for preparing a low-temperature sintered sanitary ceramic body:
[0014] S1 puts the hard raw material and water into a grinder according to the mass percentage for a first grinding;
[0015] S2 adds the soft raw material according to the mass percentage to the slurry obtained in S1 for secondary grinding;
[0016] S3 puts the slurry through grinding, sieving, and adding water and additives to the slurry;
[0017] S4 slurry injection, injecting the slurry in S3 into a mold for molding, demoulding and drying to obtain a ceramic green body;
[0018] S5 sintering, sintering the S4 ceramic green body in an electric furnace;
[0019] The hard raw materials are high-alumina porcelain stone, spodumene tailings or microcline, potassium feldspar, and boron-containing waste glass; the soft raw materials are ball clay, porcelain clay, and tremolite.
[0020] Preferably, the mass percentage of water in S1 is 25-30% of the dry basis of all hard materials; and the tool used for grinding in S1 and S2 is a ball mill.
[0021] Preferably, the particle size of the mud obtained by the first grinding is D10≤1.5μm, D50≤5.5μm, D90≤14.5μm, and the particle size of the mud obtained by the second grinding is D10≤1.5μm, D50≤7.5μm, D90≤21.0μm.
[0022] Preferably, the additive is one or both of sodium silicate and alkaline noodles, wherein the amount of sodium silicate added is 0.5-1.0% of the dry basis of all raw materials, and the amount of alkaline noodles added is 0.1-0.3% of the dry basis of all raw materials.
[0023] Preferably, the concentration of the mud in S3 is 350-360 g / 200 ml, the yield value is 8-12 dyn / cm2, the fluidity V0 is 35-55 s / 200 ml, and the slurry intake speed is 6-9 mm / 45 min.
[0024] Preferably, the highest sintering temperature in S4 is 1100° C. and the constant temperature time is 1-3 h.
[0025] The third aspect of the present invention provides a low-temperature sanitary ceramic, comprising the low-temperature sintered sanitary ceramic body described above.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The invention introduces natural micro-nano fibrous tremolite to replace dolomite, a raw material containing calcium and magnesium, as a calcium and magnesium source for low-temperature synthesis of sodium / calcium feldspar and other crystals in a low-temperature green body material system, optimizes the physical phase composition of a 1100°C low-temperature sintered (water absorption rate ≤ 0.5%) sanitary ceramic green body system, forms a multi-mineral phase with sodium / calcium feldspar as a main crystal phase and Mg-Al spinel and the like as a secondary crystal phase, realizes the key technology of steady-state control of sintering deformation rate, that is, keeps the deformation amount of the deformation curve during the heat preservation period basically unchanged and tends to be stable, broadens the sintering range of the low-temperature sintering system, solves the technical problem of regularity control of mass-produced products, and enables the low-temperature sintered ceramic slurry to have better molding performance, improves the tensile strength of wet green bodies and dry green bodies, and solves the process problems such as easy cracking during molding and sintering processes caused by poor slurry suspension. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The sintering curves of electric furnace (low temperature) and tunnel kiln (high temperature) are shown below.
[0029] Figure 2 This is a schematic diagram of the bending deformation test of electric furnace and tunnel kiln sintering.
[0030] Figure 3 Schematic diagram for comparing the TMA deformation curves of Example 2, Comparative Example 1 and Comparative Example 7,
[0031] Figure 4 The SEM diagram of the microscopic morphology of tremolite and dolomite.
[0032] Figure 5 This is a schematic diagram of the microscopic morphology SEM and energy spectrum element analysis EDS results of Example 2.
[0033] Figure 6 The XRD patterns and main phase quantitative analysis results of Example 2, Comparative Example 1 and Comparative Example 7 are shown. DETAILED DESCRIPTION
[0034] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0035] The following is a further description of a low-temperature sintered sanitary ceramic body and a preparation method and a low-temperature sanitary ceramic of the present invention through specific examples and comparative examples. The chemical composition of the raw materials used in each example and comparative example is shown in Table 1.
[0036] Table 1 Chemical composition of raw materials
[0037]
[0038] Example 1
[0039] The present embodiment provides a low-temperature sintered sanitary ceramic body, comprising the following raw materials in mass fractions: 13% ball clay, 17.5% high-alumina porcelain stone, 10.5% spodumene tailings, 35% porcelain clay, 2% potassium feldspar, 6% tremolite, and 16% boron-containing waste glass.
[0040] Preparation of low temperature sintered sanitary ceramic green body in this embodiment:
[0041] S1: high-aluminum porcelain stone, spodumene tailings, potassium feldspar, boron-containing waste glass and water are placed in a ball mill and ground with high-aluminum balls to a particle size of: D10 = 0.94 μm, D50 = 3.84 μm, D90 = 12.71 μm;
[0042] S2 adds ball clay, china clay and tremolite to the slurry obtained in S1 for secondary grinding; grinding to particle sizes of: D10 = 0.93 μm, D50 = 4.37 μm, D90 = 19.86 μm;
[0043] S3 was ground and passed through a 60-mesh sieve. Water and sodium silicate were added to control the mud concentration to 350 g / 200 ml and the yield value to 8 dyn / cm 2 , fluidity V0 is 35s / 200ml, pulp feeding speed is 6 / 45min;
[0044] S4 slurry injection, injecting the slurry in S3 into a mold for molding, demoulding and drying to obtain a ceramic green body;
[0045] S5 sintering, the S4 ceramic green body is sintered in an electric furnace, the temperature is raised to 1100°C, the temperature is kept constant for 1.5 hours, and then the temperature is lowered to 30°C; a low-temperature sintered sanitary ceramic green body is obtained. The specific sintering curve is shown in Table 2 and Figure 1 .
[0046] Table 2 Green body sintering test
[0047]
[0048]
[0049] Embodiment 2-5
[0050] This embodiment is used to compare and illustrate the low-temperature sintered sanitary ceramic body disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the difference is that the mass fraction of raw materials, mud particle size, and chemical composition are shown in Table 3-4, and the rest is consistent with Example 1.
[0051] Comparative Examples 1-6
[0052] Compared with Example 1, the differences are: the raw materials used and their mass fractions, mud particle size, and chemical composition are as shown in Table 3-4, and the rest are consistent with Example 1.
[0053] Comparative Example 7
[0054] This comparative example is a traditional high-temperature sintered sanitary ceramic body, which includes the following raw materials in mass fractions: 13% microcline, 15% kaolin, 15% low-aluminum porcelain stone, 15% ball clay, 18% high-aluminum porcelain stone, 22% porcelain clay, and 2% dolomite.
[0055] The comparative example preparation method comprises the following steps:
[0056] 1. All raw materials are mixed and ground. The particle size of the slurry after grinding is D10 = 2.19 μm, D50 = 19.48 μm, and D90 = 108.82 μm.
[0057] 2. Same as step S3 in Example 1.
[0058] 3. The slurry is injected into a plaster mold by micro-pressure grouting method. After demoulding and drying, the ceramic green body is obtained. The green body is sintered in a tunnel kiln with a maximum sintering temperature of 1200°C to test the shrinkage, deformation, deformation coefficient, bending strength and other properties. The specific sintering curves are shown in Table 2 and Figure 1 shown.
[0059] Table 3 Examples, comparative examples formulations and mud particle sizes
[0060]
[0061] Table 4 shows the chemical components of the examples and comparative examples.
[0062]
[0063]
[0064] 1. Testing the slurry properties, green body sintering temperature, and green body sintering properties of the above embodiments and comparative examples 1. Chemical composition test
[0065] The chemical composition of the ceramic blank was tested using an X-ray fluorescence spectrometer (S8 TIGER) from Bruker, Germany. The test results are shown in Tables 1 and 4.
[0066] 2. Sintering temperature test
[0067] The actual sintering temperatures of low-temperature sintering (electric furnace) and high-temperature sintering (tunnel kiln) were tested using the BTC005 temperature measuring ring (900-1200℃) and CTC011 temperature measuring ring (1100-1400℃) of Flow Corporation of the United States. The results are shown in Table 2 and Figure 1 shown.
[0068] 3. Mud particle size test
[0069] The particle size of the ground slurry was tested using a laser particle size analyzer (SALD-2201) from Shimadzu Corporation of Japan. The test results are shown in Table 3.
[0070] 4. Water absorption test
[0071] The water absorption of the ceramic body was tested using an electronic balance according to ASTM C373-88 (2006). The test results are shown in Table 5.
[0072] 5. Sintering shrinkage test
[0073] By comparing 10×20×250mm 3 The shrinkage rate of the rectangular test strip is calculated by the change in length before and after sintering, and the calculation formula is λ = (L0-L) / L0×100%. In the formula, λ is the linear shrinkage rate of the test strip; L0 is the length of the test strip before sintering; L is the length of the test strip after sintering. The test results are shown in Table 5.
[0074] 6. Standard thickness deformation test
[0075] Measurements 10×20×250mm 3 The deflection and thickness of the rectangular test bar after sintering on the refractory support with a span of 200mm are calculated by eliminating the influence of the thickness difference of the test bar and obtaining the bending deformation of the standard size test bar. The calculation formula is W = Sh 2 / 100, where W is the standard thickness bending deformation, S is the deflection of the test bar after sintering, and h is the thickness of the test bar after sintering. Figure 2 The test results are shown in Table 5.
[0076] 7. Deformation coefficient test
[0077] Measurements 10×20×250mm 3 The deflection and thickness of the rectangular test bar after sintering on the refractory support and the span of the refractory support are used to calculate the deformation coefficient of the green body material. The calculation formula is PI=4Sh2 / 3L4, where PI is the deformation coefficient, S is the deflection of the test bar after sintering, h is the thickness of the test bar after sintering, and L is the span of the refractory support. The test results are shown in Table 5.
[0078] 8. Bending strength test
[0079] The flexural strength of round rod-shaped test bars with a span length of 100 mm and a diameter of 15 mm was tested using a universal material testing machine (AG-IS) from Shimadzu Corporation of Japan in accordance with GB / T 6569-2006. The test results are shown in Table 5.
[0080] 9. Deformation curve analysis
[0081] The deformation curve of the low-temperature sintered experimental green body was obtained by using a thermomechanical analyzer (TMA) from NETZSCH in Germany to test a 15×3×6mm cuboid green body sample through a three-point bending test. The specific test conditions are: in an air atmosphere, a constant load of 0.1N is applied, and the temperature is raised to the highest temperature at a heating rate of 10℃ / min. The highest temperature for high-temperature sintering is 1200℃, and the highest temperature for low-temperature sintering is 1100℃. They are kept warm for 90 minutes respectively. In the cooling process from the highest temperature to 900℃, the cooling rate is set to 10℃ / min; in the cooling process from 900℃ to room temperature, the cooling rate is set to 5℃ / min. The analysis results are as follows: Figure 3 shown.
[0082] 10. Microscopic morphology analysis
[0083] The field emission scanning electron microscope (SEM) of Zeiss of Germany and the energy spectrum element analysis (EDS) of Oxford of the United Kingdom were used to analyze multiple samples. The analysis results are as follows: Figure 4 and Figure 5 shown.
[0084] 11. Phase analysis
[0085] The samples were analyzed by X-ray diffractometer (XRD) from Rigaku Corporation. Figure 6 shown.
[0086] Table 5 Slurry properties and firing properties of examples and comparative examples
[0087]
[0088] 2. Analysis of the results of the slurry performance, green body sintering temperature, and green body sintering performance data of the above embodiments and comparative examples
[0089] 1. As shown in Table 1, the slurries of Examples 1-5 have good suspension properties, are not easy to settle, have suitable thixotropy, and are not cracked during molding, which are significantly better than the low-temperature sintered green bodies of dolomite in Comparative Example 1 and dolomite and quartz in Comparative Example 6. Although the slurries of the low-temperature sintered green bodies of sepiolite in Comparative Example 2 and the low-temperature sintered green bodies of attapulgite in Comparative Example 3 have greater thixotropy, their suspension properties are significantly better than those of Comparative Example 1, which indicates that the introduction of natural micro-nano fibrous tremolite, sepiolite, and attapulgite to replace granular dolomite (microscopic morphology such as Figure 4 As shown in the figure, as a calcium and magnesium source for low-temperature synthesis of sodium / calcium feldspar and other crystals, it can effectively improve the suspension of mud. However, the thixotropy of natural sepiolite and attapulgite is too large, which can easily cause cracking of the green body during molding. Only tremolite has the most suitable suspension and thixotropy. It can effectively improve the crack resistance of the SiO2-Al2O3-CaO-MgO-K2O-Na2O-Li2O-B2O3 low-temperature sintered sanitary ceramic green body system during molding and firing, and improve the qualified rate of semi-finished products and finished products.
[0090] 2. From the test data of Examples 1-3 and Comparative Example 4, it can be seen that as the amount of boron-containing waste glass is gradually reduced until no addition is made, the water absorption rate of the green body increases, and the sintering shrinkage and deformation decrease, resulting in a decrease in the final bending strength. This shows that reducing the boron-containing waste glass of the present invention can increase the refractoriness and porosity of the green body.
[0091] 3. The test data of Examples 1, 5 and Comparative Example 5 show that the amount of spodumene tailings is reduced until no addition is made, the water absorption rate of the green body is increased, and the sintering shrinkage and deformation are reduced. It is shown that the spodumene tailings of the present invention can effectively sinter the green body. Example 4 replaces the spodumene tailings with an equal amount of microcline, and the comprehensive properties such as deformation, strength, and cracks are very close to those of Example 2, indicating that the two can replace each other, enriching the types of raw material selection.
[0092] 4. It can be seen from Table 5 that the standard thickness deformation and deformation coefficient of Example 2 are significantly smaller than those of Comparative Example 1. Figure 3 It can be seen that the deformation curve comprehensively characterizes the deformation rate (derivative of time) from the entire firing cycle. The deformation rate of Example 2 in the initial stage of heat preservation is significantly greater than that of Comparative Example 1. The liquid phase is formed rapidly, filling the pores of the solid particles, and vitrifying into porcelain faster. After reaching the maximum deformation quickly, the deformation curve is approximately flattened, and the material system tends to stabilize faster. This shows that the sintering range of Example 2 in the present invention is close to that of Comparative Example 7, which is wider than that of Comparative Example 1, and the steady-state range is extended. It can better adapt to the fluctuations of the kiln firing system in actual production, meet the needs of large-scale production of tunnel kilns, and ensure that the key properties such as the fired dimensional tolerance and geometric distortion of the product meet the quality requirements.
[0093] 5. By Figure 5It can be seen that in Example 2, fine spherical particles are widely distributed in the green body. EDS detection shows that these spherical particles are mainly sodium / calcium feldspar crystals containing elements such as O, Si, Al, Ca, and Na, and a small amount of needle-rod-shaped crystalline phases (Mg-Al spinel, etc.). The natural micro-nano fiber structure of tremolite provides a nucleation reaction matrix for the in-situ growth of crystals during the sintering reaction, provides Si, Al, Ca, and Mg sources for newly synthesized crystals, shortens the reaction path and reaction time, and promotes the synthesis of needle-rod-shaped and other crystalline phases. The multi-phase system composed of a large number of spherical sodium / calcium feldspar crystals and a small amount of needle-rod-shaped crystalline phases increases the viscous resistance path of the green body material system, synergistically improves the liquid phase viscosity of the system, and significantly reduces deformation.
[0094] 6. By Figure 6 It can be seen that the molten liquid phase content of Comparative Example 1, Example 2, and Comparative Example 7 increases successively, and the total amount of crystal phase decreases successively. The significant increase of the spherical sodium / calcium feldspar crystal phase in the first two plays a key role in resisting deformation; but the molten liquid phase in Comparative Example 1 is too little, resulting in a decrease in the rate of reaching the maximum deformation, that is, the sintering range is narrowed. The molten liquid phase content of Example 2 is moderate, and its rate of reaching the steady-state maximum deformation is significantly faster than that of Comparative Example 1. At the same time, it has a higher content of needle-shaped crystal phase (Mg-Al spinel, etc.), which can synergistically improve the liquid phase viscosity, has a stronger ability to resist dynamic changes in deformation, and significantly broadens the sintering range of the green body to the level of Comparative Example 7.
[0095] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A low-temperature sanitary ceramic body, characterized in that: The green body comprises the following raw materials in mass fractions: 10-20% ball clay, 10-25% high-alumina porcelain stone, 5-15% spodumene tailings or microcline, 25-45% porcelain clay, 0-10% potassium feldspar, 5-20% tremolite, and 5-20% boron-containing waste glass.
2. A low-temperature sanitary ceramic body according to claim 1, characterized in that: The chemical composition of the green body is as follows: SiO2: 50-60%, Al2O3: 15-25%, Fe2O3: 0.5-1.5%, TiO2: 0.3-1%, CaO: 4-9%, MgO: 1-6%, K2O: 2-4%, Na2O: 0.2-1.5%, Li2O: 0-0.5%, B2O3: 0.3-1.5%, and loss on ignition: 5-12%.
3. A low-temperature sanitary ceramic body according to claim 1, characterized in that: The molar ratio of SiO2 to Al2O3 is (4-6):1, and the molar ratio of K2O to (Na2O+Li2O) is (2-6):
1.
4. A low-temperature sanitary ceramic body according to claim 1, characterized in that: The tremolite is a fibrous crystal with a fiber length D50 of 10-30 μm and a diameter of ≤0.5 μm.
5. A method for preparing a low-temperature sanitary ceramic body according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1 puts the hard raw material and water into a grinder according to the mass percentage for a first grinding; S2 adds the soft raw material according to the mass percentage to the slurry obtained in S1 for secondary grinding; S3 puts the slurry into the mill, sieves it, and adds water and additives to the slurry; S4 slurry injection, injecting the slurry in S3 into a mold for molding, demoulding and drying to obtain a ceramic green body; S5 sintering, sintering the S4 ceramic green body in an electric furnace; The hard raw materials are high-alumina porcelain stone, spodumene tailings or microcline, potassium feldspar, and boron-containing waste glass; the soft raw materials are ball clay, porcelain clay, and tremolite.
6. The method for preparing a low-temperature sanitary ceramic body according to claim 5, characterized in that: The particle size of the mud obtained by the first grinding is D10≤1.5μm, D50≤5.5μm, D90≤14.5μm, and the particle size of the mud obtained by the second grinding is D10≤1.5μm, D50≤7.5μm, D90≤21.0μm.
7. The method for preparing a low-temperature sanitary ceramic body according to claim 5, characterized in that: The concentration of the mud in S3 is 350-360g / 200ml, the yield value is 8-12dyn / cm2, the fluidity V0 is 35-55s / 200ml, and the slurry intake speed is 6-9mm / 45min.
8. The method for preparing a low-temperature sanitary ceramic body according to claim 5, characterized in that: The additive in S3 is one or both of sodium silicate and alkaline noodles, wherein the amount of sodium silicate added is 0.5-1.0% of the dry basis of all raw materials, and the amount of alkaline noodles added is 0.1-0.3% of the dry basis of all raw materials.
9. The method for preparing a low-temperature sanitary ceramic body according to claim 5, characterized in that: The highest sintering temperature in S5 is 1100°C and its constant temperature time is 1-3h.
10. A low-temperature sanitary ceramic, characterized in that: It comprises a low-temperature sanitary ceramic blank as described in any one of claims 1 to 4 or a low-temperature sanitary ceramic blank prepared by the method as described in any one of claims 5 to 9.
Citation Information
Patent Citations
Kaolin porcelain body and application method thereof
CN109305795A
Low-temperature sintered sanitary ceramic green body and preparation method thereof
CN113929437A
High-whiteness and high-strength ceramic body, ceramic product and preparation method of high-whiteness and high-strength ceramic body
CN114105607A
Single-step glazing method with opal ti-zn system at medium or high temp.
CN86105759A
High strengthened partially crystallized silicate bodies and ceramics used to the composition of anorthite, diopside system crystallized frit
KR1020130075157A